81 Leading the way towards parity of esteem. (3rd November 2019) - Ahmed, Hanad; Alexopolous, Arion; Compton, Alex; Otto, Rita; Sanders, Gabrielle; Patel, Yusuf
Abstract : Mental health (MH) problems account for more than a quarter of the UK's disease burden, with an estimated economic cost of £105 billion a year. Three quarters of chronic MH problems start before age 18. With the absolute rise in population mental ill-health, this problem is only set to grow. As the economic cost grows, this is an issue that will affect all- not just those with mental ill-health. Assessment of the current situation and government plans identified some of the causes leading to poor Mental Health care. Using the Pareto Principle to stratify the causes, three key areas were identified: Children & Adolescents, Community Training and Data Collection & Research. The findings of this work have been presented to students and academics at Imperial College London. Within each of these three areas, recommendations for the next five years offer an opportunity for healthcare professionals, primary care workers in particular, to support a healthier population and greater patient satisfaction. Implementation of these recommendations requires careful management and strong vision and leadership from healthcare professionals.